Digital Promotion, Technology, and Impulsive Buying Among Generation Z: An Islamic Finance Perspective - Naili Jazilinni'am; Dina Fitrisia Septiarini; Rahmad Hidayat; M Habib Azhari (Jurnal Informatika Ekonomi Bisnis, 2026)
The development of digital technology has driven significant changes in consumer behavior, particularly among Generation Z. The ease of access to online shopping platforms has made this generation highly responsive to visual and emotional promotions, rendering them more susceptible to impulsive buying behavior. This study aims to analyze the influence of technology, promotion, and religiosity on impulsive buying behavior among Generation Z. This quantitative research employed a questionnaire distributed through online channels and collected responses from 173 participants in Indonesia. Data analysis and hypothesis testing were conducted using the Structural Equation Modeling (SEM) method. The results indicate that technology (β = 0.383) and promotion (β = 0.359) have a positive and significant effect on impulsive buying behavior. Meanwhile, religiosity (β = -0.103) shows a negative but statistically insignificant effect on impulsive buying behavior. These findings suggest that although religiosity may contribute to reducing impulsive buying tendencies, its influence is not strong enough to significantly affect purchasing behavior among Generation Z consumers in the digital environment.